2012
DOI: 10.1007/s10750-012-1181-2
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation, phenology and disturbance of macroinvertebrates in temporary water bodies

Abstract: The temporal transition of species dominance following disturbances is strongly influenced by taxon life histories. In temporary water bodies, seasonal progression can be rapid. The community response of aquatic littoral invertebrate communities to disturbance was measured across four temporary water bodies (turloughs) representing a hydroperiod gradient in the karst landscape of western Ireland. Three distinct turlough wet-phases were identified based on macroinvertebrate taxon richness and community composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 41 publications
2
19
0
1
Order By: Relevance
“…This result agrees with Porst et al (2012), Vanschoenwinkel et al (2009), passive dispersers are more affected by the hydroperiod than active ones due to their low dispersal ability, which makes them, in general, permanent inhabitants of temporary ponds. In contrast, some groups, like Coleoptera, Hemiptera, Ephemeroptera and most Chironomidae, are considered cyclic colonizers that inhabit temporary habitats during the wet phase and migrate to permanent systems to avoid dry conditions (Williams, 1987).…”
Section: Discussionsupporting
confidence: 89%
“…This result agrees with Porst et al (2012), Vanschoenwinkel et al (2009), passive dispersers are more affected by the hydroperiod than active ones due to their low dispersal ability, which makes them, in general, permanent inhabitants of temporary ponds. In contrast, some groups, like Coleoptera, Hemiptera, Ephemeroptera and most Chironomidae, are considered cyclic colonizers that inhabit temporary habitats during the wet phase and migrate to permanent systems to avoid dry conditions (Williams, 1987).…”
Section: Discussionsupporting
confidence: 89%
“…As predicted, the communities showed differential composition and abundance between the wet and dry season enhancing to the global diversity in the Itupararanga reservoir. The presence of aquatic macrophytes, especially the floating species, during the wet season, as well as the inundation of adjacent areas due to the rising water level, are factors that must be considered in order to interpret the seasonality (Porst et al, 2012;Schultz and Dibble, 2012). It should be observed that the lower range values recorded during the dry season indicate more stable conditions in the environment, once that fewer fluctuations of the variables have occurred for this period.…”
Section: Discussionmentioning
confidence: 99%
“…In the turloughs, the 1-month interval was deemed appropriate based on the findings of previous studies such as Gill (2010), who, in an attempt to optimise sampling methodologies, evaluated nutrient concentrations both spatially and temporally and found 1 month to be an adequate sampling interval. This 1-month interval has also been used as an established sampling technique for a variety of other ecohydrological turlough studies (Cunha Pereira, 2011;Cunha Pereira et al, 2010;Porst et al, 2012;Waldren, 2015).…”
Section: Hydrochemistrymentioning
confidence: 99%